Stochastic evaluation of restoration procedures on postmining land areas using a game theory approach. (28th December 2021) - Vach, Marek; Vachová, Pavla; Walmsley, Alena; Berka, Martin; Albert, Jan; Cienciala, Emil; Braun Kohlová, Markéta; Máca, Vojtěch; Melichar, Jan
Abstract: Restoration of postmining areas is a frequently addressed topic requiring a comprehensive view. In this article, the recovery process of selected postmining spoil heap sites was evaluated using an approach based on calculation of Nash equilibrium (NE) probability distributions. Many of these sites have been allowed to recover by spontaneous succession, while on others, a variety of restoration procedures have been tested, most of them variants of the forest plantation type. The evaluation was carried out on selected data from each site that reflects four factors: the richness of the vegetation cover, the amount of biomass as soil macrofauna per unit area, the forestry yield, and the attractiveness for recreation use. The analysis was based on permuted game configurations in which these factors were treated as competing entities, adversaries that were differentially successful in each location depending on the conditions of the recovery procedure used. The game strategies that the factors exhibited as theoretically interacting entities had no primary information content, which meant that they could be treated stochastically. The result was a distribution of the NE probability at each location. Considering the fact that this result reflected the degree of optimality of the included factors, the calculation could be considered as a specific type of multicriteria evaluation, which was practically applicable and provided unambiguous results. The NE probability in sites restored by deciduous tree stands was higher, which was therefore assumed to correspond to higher stability.